Impact of single nucleotide polymorphisms (SNPs) in antioxidant-enzyme genes on the concentrations of folate, homocysteine and glutathione in plasma from healthy subjects after folic acid supplementation – a randomized controlled crossover trial - Mansoor, Mohammad Azam; Stea, Tonje Holte; Slettan, Audun; Perera, Erandie; Maddumage, Ridmi; Kottahachchi, Darshana; Ali, Dhikra Saleem; Cabo, Rona; Blomhoff, Rune (Genes & nutrition, 2025)
One-carbon metabolism links folate and methionine metabolism and this is essential for nucleotide synthesis in the cells. Alterations in one-carbon metabolism are associated with cardiovascular disease (CVD), type 2 diabetes and cancer. Our aim was to investigate whether SNPs in antioxidant-enzyme genes impact the concentrations of folate in serum (s-folate), plasma total homocysteine (p-tHcy) and total glutathione in plasma (p-tGSH) in healthy subjects after supplementation with folic acid. In a randomized, double blind, crossover study, healthy subjects received 0.8 mg folic acid per day or a placebo for two weeks. Twenty-four male, and sixty-seven female subjects participated in this study. Participants were aged 36.4 ± 14.8 years (mean ± SD). We studied SNPs in six genes by PCR methods. The concentrations of s-folate, p-tHcy and p-tGSH were measured in fasting samples with Cobas and an HPLC-fluorescence method. Student T-tests and ANOVA were used for the statistical calculations. The subjects with SNP (rs4880) in superoxide dismutase (SOD2) gene (CC) allele had higher concentrations of s-folate and lower concentrations of p-tHcy than subjects with (CT + TT) alleles, (p = 0.014 and p = 0.012). Contrary to SOD2 (CC) allele, the subjects with SNP (rs1001179) catalase (CAT) CC allele had lower concentrations of s-folate (p = 0.029), higher concentrations of p-tGSH (0.017) and higher concentrations of p-tHcy before and after folic acid supplementations (p = 0.015, p = 0.017) than the subjects with (CT + TT) allele. Glutathione transferase (theta)1 (GST-T1) genotype was associated with higher concentrations of s-folate than GST-T0 before (p = 0.025) and after folic acid supplementation (p = 0.047). SNP (rs1050450) in glutathione peroxidase (GPX1) had also impact on the concentrations of p-tGSH (p = 0.011) in healthy subjects. SNPs in SOD2 (rs4880), CAT (rs1001179), and GST1 impact the concentrations of s-folate, and p-tHcy in healthy subjects before and after folic acid supplementation. Our findings suggest that SNPs in antioxidant-genes have a role in health and disease by impacting the concentrations of s-folate, p-tHcy and p-tGSH.